Selling Celebrities: The Intertextuality of Celebrity Scandals in The Drama Taxi Driver and Burning Sun Documentary - Baiti, Aulia Muthoharoh Nur; Azizah, Dini Alif; Pagelaran, Rizka Rachma; Ghoniyy, Aulia Rahma; Putri, Laila Rohmatika Nurida (RADIANT: Journal of Applied, Social, and Education Studies, 2025)
Scandal refers to news about actions or statements of individuals or groups that violate the law or moral principles. Scandals trigger public reactions, political trials, and legal investigations. This study examines the intertextuality of celebrity scandals as depicted in the South Korean drama Taxi Driver season 2 and the documentary Burning Sun. Using Riffaterre's Intertextuality theory (1990), the research explores the relationship between these two media texts, focusing on how fictional and factual narratives adapt and reinterpret real-life events. The qualitative descriptive method is employed to analyze plot and setting elements, revealing both obligatory and aleatory intertextual connections. The findings highlight how Taxi Driver dramatizes the Burning Sun scandal with creative liberties, such as fictional names and exaggerated plots, while the documentary adheres to factual reporting. The study underscores the role of intertextuality in bridging fiction and reality, offering insights into how media shapes public perception of scandals involving power, exploitation, and justice.